EVALUATION OF ANTIMICROBIAL AND ANTICANCER EFFICACY OF PURIFIED SERRAPEPTASE ENZYME - Dalia Elebeedy, Aml Ghanem, Marwa El-Sayed, Ingy Badawy, Alya Redhwan, Mashail A. Alghamdi, Tahani M. Alqahtani, Enas A. Almanzalawi, Majid Al-Zahrani, Asmaa S. Abdelgeliel (Chelonian Research Foundation, 2024)
Background: Proteolytic enzymes have been used for different therapeutic purposes. Serrapeptase has versatile authenticated applications due to its immense properties. Our study aimed to investigate the antibacterial and anticancer effect of serrapeptase enzyme. Methods: Serrapeptase was purified from the supernatant of bacterial culture and precipitated using ammonium sulfate. Antibacterial activity was assessed against multiple bacterial strains by microdilution method. Anticancer activity of serrapeptase against three cancer cell lines (A549, Caco, MCF7) was evaluated by measuring cytotoxicity through MTT assay. Serrapeptase induced apoptosis was assessed by measuring activity of caspase-3 and flow cytometry measurement using annexin kit. Results: The lowest MIC (minimum inhibitory concentration) of serrapeptase was for K. pneumonia (2.94 µg/mL) while the highest values were for P. aeruginosa, and MRSA (MIC= 47 µg/mL). S. aureus, E. coli, S. enterica, P. mirabilis, and C. albicans had the same MIC (5.88 µg/mL). MTT assay showed that the lowest IC50 (half-maximal inhibitory concentration) values were for A549 and MCF7 cell lines (IC50 =1.59 µg/mL and 1.15 µg/mL respectively). Assessment of apoptosis revealed increase caspase-3 activity and percentage of early apoptotic cell in treated A549 and MCF7 cell lines.Conclusion: This study showed promising effects of serrapeptase as an antibacterial and anticancer agent that need to be validated by more in-vivo and mechanistic studies